2015
DOI: 10.21608/jappmu.2016.52748
|View full text |Cite
|
Sign up to set email alerts
|

Age of Puberty and Fertility of Male New Zealand White Rabbits Orally Administered With Royal Jelly or/ and Bee Honey

Abstract: The present study was designed to investigate the effects of royal jelly (RJ) or/ and bee honey (H) on age of sexual puberty, semen quality and fertility of male New Zealand White (NZW) rabbits. Eighty pre-pubertal male NZW rabbits and 80 hybrid nonparous female rabbits were used in the present study. Male rabbits were randomly divided into 4 groups (20 bucks per group), bucks were administered orally with 0.5 mL of a solution/ kg body weight (BW), 3 times weekly for 6 weeks; which contained: 1) water for cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…These findings are in agreement with those of El-Hanoun et al (2014), which indicated that the sexual libido was significantly reduced in V-line rabbit bucks, which received RJ at 100 and 150 mg/kg than that of the control group. Also, Khadr et al, (2015) found that the reaction time (RT) of male NZW rabbits treated with both of royal jelly and honey decreased significantly (P<0.05) as compared with those of the control group. Similarly, the findings of Elnagar (2010) showed that the sexual libido and semen characteristics of rabbit bucks administrated with royal jelly or/ and honey increased significantly than those of the control.…”
Section: Semen Physical Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings are in agreement with those of El-Hanoun et al (2014), which indicated that the sexual libido was significantly reduced in V-line rabbit bucks, which received RJ at 100 and 150 mg/kg than that of the control group. Also, Khadr et al, (2015) found that the reaction time (RT) of male NZW rabbits treated with both of royal jelly and honey decreased significantly (P<0.05) as compared with those of the control group. Similarly, the findings of Elnagar (2010) showed that the sexual libido and semen characteristics of rabbit bucks administrated with royal jelly or/ and honey increased significantly than those of the control.…”
Section: Semen Physical Characteristicsmentioning
confidence: 98%
“…Through the last thirty years, it became important to produce safe animal and poultry products by using natural resources as different feed additives (herbal seed, bee pollen, royal jelly and propolis) which improve their production performance without any adverse effects (El-Neney andEl-Kholy, 2014 andKhadr et al, 2015).…”
mentioning
confidence: 99%
“…This result was agreed by [34] in which it showed that oral administration of royal jelly at any level could be used beneficially to have earlier puberty age, improve semen quality and fertility of male rabbits. [35] Concluded that supplementation of RJ in freezing extender can improve the cryosurvival rate and in vitro fertilizing capacity of buffalo bull sperm.…”
Section: Discussionmentioning
confidence: 56%
“…Numerous previous research reports claimed affirmative impacts of RJ on reproductive efficiency and hormonal regulation of animals (Khadr, Abdou, & El-Sherbiny, 2015;Mahdivand et al, 2019;Yang et al, 2012). Furthermore, RJ is excessively rich in essential minerals such as iron, potassium, zinc, magnesium and copper (Table 1).…”
Section: Rj Comprises Several Essential Nutritional Compounds Imperativementioning
confidence: 98%
“…The oral treatment of male rats with RJ (1 g/kg BW) significantly augmented the testis weight and the epididymis body (Hassan, 2009). Khadr et al (2015)…”
Section: Minerals and Vitaminsmentioning
confidence: 99%